Inclusion in the Early Years. - Nutbrown, Cathy; Clough, Peter, 1949-; Atherton, Frances (Los Angeles : SAGE, 2013)
This text provides an overview of inclusive education theory & practice within early years education. Written for students on early years courses as well as for practitioners in the early years sector, it provides an overview of theory in inclusive education in the early years, together with a summary of practical implications.
Previous edition: 2006.
Includes bibliographical references and index.
Keywords: Inclusive education; Early childhood education; Education